Pemberdayaan Masyarakat Melalui Pembentukan KUBE untuk Meningkatkan Kreativitas Usaha dan Kesejahteraan di Desa Ubung Kabupaten Lombok Tengah - Ni Luh Putu Anom Pancawati; I Nyoman Jajus Artana; I Nengah Dede Juliarse; Kadek Ratna Dewi (Jurnal Pengabdian UNDIKMA, 2022)
This community service aims to empower the community in the economic field by developing ideas, innovation and business creativity as well as forming collective business groups to optimize the business carried out and improve the economic welfare of the community. This service method uses lectures and education related to entrepreneurship and accounting as well as socializing the formation of business groups with the community using activity instruments in the form of focus group discussions with qualitative descriptive data analysis. This service involves community members who are of productive age and teenagers who are active in youth organizations in the local environment. The conclusion of this service is that the Keraning community of Ubung Village together agreed to form a joint business group under the name Jemet Mekarya for the benefit of all residents engaged in the milling business. Through the joint business group, it is hoped that the creativity of the community's business will be stimulated and the economic welfare of the community will increase.